Extrinsic wheat fibre consumption enhances faecal bulk and stool frequency; a randomized controlled trial. Issue 2 (17th January 2019) - de Wit, Nicole; Esser, Diederik; Siebelink, Els; Fischer, Anne; Sieg, Juergen; Mes, Jurriaan
Abstract : Consumption of extrinsic wheat fibre-enriched products shows beneficial effects on faecal bulk and stool pattern. Abstract : The beneficial effect of wheat fibres on faecal bulk and stool pattern has mainly been observed with intact wheat fibres. This study investigates the effect of extrinsic wheat fibre (VITACEL® wheat fibre), which can be easily incorporated in many food products, on faecal bulk, stool pattern, gastrointestinal complaints, satiety and food liking. In a double-blind randomized crossover trial, healthy male volunteers received meal boxes for 10 days, containing various food products enriched with extrinsic wheat fibre (∼20 grams of additional fibre per day) or control food products containing conventional levels of fibre with similar taste, appearance and caloric values. Meal boxes were integrated in the normal dietary pattern. Stool frequency, stool consistency, gastrointestinal complaints, satiety and product liking were assessed daily, and the last 5 days of each intervention, participants collected all their faeces to analyse faecal bulk. We found that consumption of extrinsic wheat fibre-enriched products significantly enhanced faecal bulk; faecal wet and dry weight showed a 1.41 ± 0.1 and 1.55 ± 0.1 times increase compared to control, respectively ( p < 0.01). Extrinsic wheat fibre intervention furthermore increased stool frequency (1.3 ± 0.1 defecations per day compared to 1.1 ± 0.1 defecations per day during control diet, p < 0.05), but did not affect stool consistency, satiety, gastrointestinal complaints or product liking. So, increased consumption of extrinsic wheat fibre enhances faecal bulk and stool frequency. As this extrinsic wheat fibre can be easily incorporated in many food products without affecting appearance or taste, it might facilitate the increase of overall fibre intake and subsequently improve (intestinal) health.